Early use of 'open-air' treatment for 'pulmonary phthisis' at the Dreadnought Hospital, Greenwich, 1900–1905. Issue 884 (1st June 1999) - Cook, G C
Abstract : The use of open-air treatment for tuberculosis ('pulmonary phthisis') at the Dreadnought Hospital, Greenwich from 1900 to 1905 is reviewed. A marked reduction in mean mortality rate compared to 'orthodox' management was observed.